Validity, Practicality E-Module Global Warming, Guided Inquiry to Improve Students' Creative Thinking Skills - Ahmad Fauzi; Rahmi Habibah (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to produce a physics e-module on global warming mitigation material based on guided inquiry with valid and practical categories. The type of research used is Research and Development development research. The research model used is the Van Den Akker development model. This model consists of four stages, namely preliminary research, prototyping stage, summative evaluation and reflection and documentation. The data used in this study are needs analysis data, validation and practicality. The instruments used are preliminary questionnaires, validation sheets, and practicality sheets. Data analysis techniques for needs analysis and practicality tests use descriptive analysis, analysis of validity using the Aiken's V formula. The results of this study are that the physics e-module on global warming mitigation material based on guided inquiry is in the valid category and the practicality level of the e-module is in the very practical category by teachers and students.